Experimental Evaluation of Exhaust Emission Characteristics and Fuel Consumption of an F8A Engine with HHO Electrolyzer Addition - Rafly Pratama; Muhammad Darrul Salim Istara; Yusep Sukrawan; Tatang Permana (Universitas Negeri Padang, 2026)
Growing vehicle use has increased interest in combustion additives that may reduce fuel use and exhaust emissions in conventional engines. This study evaluated an HHO-based electrolyzer system applied to a carburetted F8A engine without internal engine modification. An experimental comparison was conducted under standard operation without HHO and with an active electrolyzer at 800, 2000, 3000, and 4000 rpm. The measured parameters were CO, CO₂, HC, O₂, lambda, and fuel consumption. HHO addition reduced HC emissions by 14.2%, decreased O₂ by 18.5%, increased CO₂ by 10.9%, and shifted lambda from 1.197 to 1.124, indicating a movement toward more complete combustion. However, CO increased by 10.0%. Fuel consumption decreased by 7.0% at 800 rpm, 7.3% at 3000 rpm, and 9.8% at 4000 rpm, but increased by 4.5% at 2000 rpm. These findings indicate that HHO addition can modify the emission profile and fuel consumption of a carburetted F8A engine, although its benefits are engine-speed dependent.